FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN PERUSAHAAN - Imaniar, Fitrah Qulukhil; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The timeliness of the submissionof financial statement is an important thing, because the information in the financial statement is used by the user in decision making. When financial statement is submitted immediatelly, the information in the financial statement becomes useful, and the user of financial statement can makea better decisionfromboth aspectseither quality or time. This research is meant to test some factors which influence to the timeliness of the submission of financial statement of manufacturing companies which are listed in Indonesia Stock Exchange. The factors which are tested in this research are profitability, audit opinion, firm size, and firm age.The samples in this research are manufacturing companies which are listed in Indonesia Stock Exchange (IDX) in 2010-2014 periods. The data in this research is the secondary data and the sample selection has been carried out by using purposive sampling method. Analysis instrument has been done by using multiple linear regressions analysis with the significance level is 5%. The samples are 65 companies with five yearobservation periods so that 325 observation objects have been selected.The result of this research shows that profitability, audit opinion, firm size, and firm age do not have any influence to the timeliness of the submission of financial statement of manufacturing companies which are listed in Indonesia Stock Exchange (IDX).Keywords: timeliness, profitability, audit opinion, firm size, firm age.